The Growing Spectrum of DADA2 Manifestations—Diagnostic and Therapeutic Challenges Revisited - Carolin Escherich; Benedikt Bötticher; Stefani Harmsen; Marc Hömberg; Jörg Schaper; Myriam Ricarda Lorenz; Klaus Schwarz; Klaus Schwarz; Arndt Borkhardt; Prasad Thomas Oommen (Frontiers in Pediatrics, 2022)
Deficiency of Adenosine Deaminase Type 2 (DADA2) is a rare autosomal recessive inherited disorder with a variable phenotype including generalized or cerebral vasculitis and bone marrow failure. It is caused by variations in the adenosine deaminase 2 gene (ADA2), which leads to decreased adenosine deaminase 2 enzyme activity. Here we present three instructive scenarios that demonstrate DADA2 spectrum characteristics and provide a clear and thorough diagnostic and therapeutic workflow for effective patient care. Patient 1 illustrates cerebral vasculitis in DADA2. Genetic analysis reveals a compound heterozygosity including the novel ADA2 variant, p.V325Tfs*7. In patient 2, different vasculitis phenotypes of the DADA2 spectrum are presented, all resulting from the homozygous ADA2 mutation p.Y453C. In this family, the potential risk for siblings is particularly evident. Patient 3 represents pure red cell aplasia with bone marrow failure in DADA2. Here, ultimately, stem cell transplantation is considered the curative treatment option. The diversity of the DADA2 spectrum often delays diagnosis and treatment of this vulnerable patient cohort. We therefore recommend early ADA2 enzyme activity measurement as a screening tool for patients and siblings at risk, and we expect early steroid-based remission induction will help avoid fatal outcomes.